Metabolic redirection and capacity expansion in heterotroph-reinforced microalgae-methanotroph systems under high ammonia stress - Yong-Ze Lu; Jia-Sen Yang; Xin-Ya Tan; Yi-Ru Wang; Hong-Yin Sha; Hao-Yu Wang; Shao-Jie Zong; Guang-Can Zhu (Bioresource Technology, 2027)

Chemical constituents from the aerial parts of Clematis terniflora DC - Meng-Ya Chen; Zi-Han Zhu; Xin-Yu Yu; Ya-Ru Wu; Shi-Hui Qian; Zhen-Lin Li (Biochemical Systematics and Ecology, 2027)

Structure and characteristics of quercetin-loaded starch nanoparticles and their surface charges for protein corona formation with gastrointestinal digestive enzymes - Yu-Ru Wu; Zhi-Yuan Yang; Shan-Dan Zhao; Dan-Yang Shen; Ya-Jun Lin; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2026)

PbrFEN-1 positively regulates pear pollen tube growth and is involved in the self-incompatibility response - Zhi-Heng Sui; Yi-Peng Ye; Ju-Yang Yao; Ya-Ru Wang; Ying Xu; Ce-Xian Cui; Shao-Ling Zhang; Chao Gu (Plant Reproduction, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Asymmetric introgression and reticulate evolution result from palaeoclimate-driven range dynamics of the Smilax hispida group in North and Central America - Xin-Yi Fan; Han-Yang Lin; Ya-Lu Ru; Yun-Peng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Antioxidant Activity of Bioactive Peptides Derived from Ulva prolifera in HaCaT Cells and Zebrafish - Li-Ru Hong; Shuo-Qi Wang; Ting-Ting Wu; Zhi-Ru Chen; Mo Chen; Chun-Er Cai; Pei-Min He; Ya Zhao; Rui Jia (Marine Biotechnology, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Optimized green extraction of flavonoids from Lycium barbarum leaves using betaine-ethylene glycol NADES: Mechanisms, identification, and bioactivity - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Xin-Yue Zhang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Activation-optimized anti-CD3 valency control enables combinatorial discovery of multi-specific nanoantibodies for solid tumor immunotherapy - Long Zhu; Ya-Jing Ma; Jian-Kang Kang; Xiu-Hai Che; Dong-Kun Zhao; Yin-Yi Cai; Yao-Ru Yu; Song Shen; Jun Wang (Science Bulletin, 2026)

Waste cotton textiles-derived cellulose superhydrophobic aerogel for efficient oil-water separation - Ya-hui Li; Hui-Jiang; Xiao-quan Zhu; Ru-ru Ma; Er-min Zhou; Jun-li Luo; De-qiang Li; Hong-tao Jia; Jun Li; Lu-xiang Wang (Journal of Water Process Engineering, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Curcumol induces autophagy-dependent hepatic stellate cell death through methionine metabolism disruption - Yi-jie Gao; Ya Zhou; Yi-ning Li; Kai-yao Yang; Si-wei Xia; Meng-ru Hu; Yang Li; Li Chen; Fei-xia Wang; Shuai Lu; Na-qi Lian; Shi-zhong Zheng; et al. (Toxicology and Applied Pharmacology, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Green and efficient extraction of polyphenols from Lycium barbarum leaves using a betaine-based natural deep eutectic solvent: Process optimization, mechanistic elucidation, and bioactivity evaluation - Ya-Jie Yuan; Zhen Liu; Yu-Ru Wang; Jing-Yi Wang; Qian Ma; Cen Xiang; Jun-Wei Yu; Yu-Ou Teng (Food Chemistry, 2026)

Superoxide dismutase/peroxidase-like MoS2 quantum dots enhance ammonia synthesis by Klebsiella pasteurii - Meng-Xin Zhao; Si-Ru Chen; Shan-Shan Hu; Ting-Ting Liu; Jia-Le Teng; Ya-Wen Yu; Jia-Long Zhang; Xue-Ru Zhou; Qun-Feng Ye; Su-Fang Qin; Le-Xing You (Journal of Environmental Chemical Engineering, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

A novel dual-function biosensor based on polarity reversal of MFC for bioelectricity generation and detecting trimethylamine-N-oxide - Sheng-chao Gao; Yu-xuan Wang; Yong-dong Li; Ru-meng Zhang; Ya-nan Zhang; Jin-song Dong; Hong-xia Ni; Yi Chen; Xi-hui Shen; Ying Liu (Chemical Engineering Journal, 2026)

Systematic metabolic engineering of Corynebacterium glutamicum for enhancing L-isoleucine production - Zhi-Han Gong; Ya-Ru Zhang; Jian-Zhong Xu (Systems Microbiology and Biomanufacturing, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

The unique biogenesis pathway of extracellular vesicles in Hirudo nipponia salivary gland cells - Ya-Li Zhu; Meng-Xiang Jia; Ru-Yu Qu; Qian Li; Xia Qiu; Wen-Chen Zhao; Yuan-Yuan Luo (Tissue and Cell, 2026)

Constructing diverse spinel/V2CTx heterostructures with tailored interfacial electron coupling for efficient oxygen evolution reaction - Li Dong; Shuang Li; Min Hu; Keke Li; Ya-Pan Wu; Xue-Qian Wu; Guangtong Hai; Cheng-Bin Zhong; Ru-an Chi; Dong-Sheng Li (Chemical Engineering Journal, 2026)

Efficient Biosynthesis of Selenium-Enriched Saccharomyces cerevisiae via Siderophore-Assisted selenite uptake and biotransformation - Wen-tao Du; Ya-ru Wei; Xue Zhao; Qiang-qiang Gou; Omer Hassan Ali; Wen-di Wang; Jia-nan Xu; Zai-ping Feng; Xin-guo Zhang (Bioresource Technology, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Recyclable Na-Mn-O nanocomposite for dual-modal photothermal/ROS antibacterial therapy against multidrug-resistant bacteria in pathogen-laden wastewater - Zhi-ru Tao; Shu-xian Hou; Yi-mei Wang; Xue-chao Shi; Xin-xin Liu; Jun Ge; Yu-han Ji; Ya-qi Cheng; Zi-yi Leng; Xin-yv Cao; Rong-rong Li; Jin-nan Xuan; et al. (Journal of Water Process Engineering, 2026)

Spermidine carbon quantum dots as an alternative antimicrobial agent for hatcheries rearing Pacific white shrimp (Litopenaeus vannamei) - Hung-Yun Lin; Han-Tso Lin; Yun-Ru Chiang; Ya-Yun Lu; James Pan; Hou-Ju Lin; Wan-Ching Kuo; Han-Jia Lin; Han-You Lin (Aquaculture, 2026)

Zinc isotopes equilibrium fractionation induced by α-Al2O3 surface adsorption and its implications: A density functional theory study - Yin-Chuan Li; Hai-Zhen Wei; Martin R. Palmer; Ya-Ru Zhou; Hao-Long Li; Zhi-Jie Liu; Yong-Hui Li (Geochimica et Cosmochimica Acta, 2026)

A dramatic drop in Nb solubility during fractional crystallization of carbonatites triggers Nb ore formation - Ya-Ting Xu; Ru-Cheng Wang; Xu-Dong Che; Fabrice Gaillard; Marion Louvel; Giada Iacono-Marziano; Johann Tuduri (Geochimica et Cosmochimica Acta, 2026)

Synergistic microbial co-culture of Saccharomyces cerevisiae and Clostridium kluyveri enhances ethyl hexanoate production for stable flavor synthesis in strong-flavor Baijiu - Qiumei Zhang; Ru Zhang; Xi Chen; Meiyue Han; Ya Zhang; Weiwei Li; Xiuting Li; Jianxiong Hao; Baoguo Sun (Food Bioscience, 2026)

Microbial-electrochemical driven simultaneous biogas upgrading and high-value medium-chain carboxylic acid production - Ya-Ru Wang; Chuan Chen; Shu-Tong Wu; Zi-Han Wang; Lei Zhao; Juan Tong; Kai-Kai Wu; De-Feng Xing; Ai-Jie Wang; Nan-Qi Ren (Bioresource Technology, 2026)

Continuous Removal of Fluoride by Fe/Al-Anchored Bamboo Charcoal in Fixed Bed Column and Prediction of Breakthrough Curve using Artificial Neural Network Model - Shuqin Bai; Ru Ya; Wei Ding; Xiaohua Xie; Mingjun Zhou; Guojing Zhao; Tianxu Yang (Water, Air, & Soil Pollution, 2026)

Prediction Of Relative Permeability Curve Based On Machine Learning Driven By Logging Data - Jia-ru Zou; Shou-dong Huo; En-liang Liu; Tong-sheng Zeng; Lian-lian Hu; Ya-ying Song; Meng Li (Applied Geophysics, 2025)

Mechanistic advances in hyperuricemia and anti-hyperuricemia therapies - Mingyue Ao; Xi Zhang; Ru Chen; Chun Xiao; Yinhua Liu; Min Gao; Ya Zhang (PharmaNutrition, 2025)

Designing light-guiding carriers in microalgal-bacterial systems: From optimization to integration and development perspectives - Cong-Cong Tang; Jin-Qiao Liu; Yong-Qi Cheng; Ya-Ru Hu; Zhang-Wei He; Wen-Qiong Wang; Zhi-Hua Li; Xiaochang C. Wang; Yu Tian (Chemical Engineering Journal, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

PcSRB cooperates with TLR2 and promotes phagocytosis and antimicrobial peptides expression - Meng-Ke Shan; Jing-Xin Dai; Wen-Ya Li; Jing-Ru Zhu; Gui-Wen Yang; Hui-Ting Yang (Fish & Shellfish Immunology, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Potassium isotopic equilibrium fractionation induced by clay adsorption and incorporation: A density functional theory study - Yin-Chuan Li; Hao-Long Li; Hai-Zhen Wei; Martin R. Palmer; Yong-Hui Li; Ya-Ru Zhou (Geochimica et Cosmochimica Acta, 2025)

Structural characterization, interaction mechanism and thermal stability of dual-fibrous complexes formed by rice glutelin fibrils and cellulose nanocrystals - Yi-Xuan Jiang; Ya-Ru Wang; Qin Yang; Xiao-Hong Yu; Han-Qing Chen (Food Chemistry, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Fabrication of superhydrophobic PDMS/EP/ODA-MWCNT/MXene@PT electrode with electroactive shape memory effect for enhanced response stability - Ya-ru Ding; Hao-jie Zhang; Yi-fan Wang; Zhe Jia; Rang-tong Liu; Jing-jing Wang (Chemical Engineering Journal, 2025)

A bioluminescent enzyme immunoassay based on nanobody-nanoluciferase fusion protein for the detection of fenpropathrin - Luo-Ji Yang; Lin Luo; Ai-Fen Ou; Hao-Sheng Zheng; Ya-Ru Li; Qileng Aori; Änatoly V. Zherdev; Zhen-Lin Xu (Food Bioscience, 2025)

Fabrication of superhydrophobic electron-conducting hydrogel e-skin with linear sensitivity for underwater monitoring - Ya-ru Ding; Yi-fan Wang; Hao-jie Zhang; Zhe Jia; Jing-jing Wang (Chemical Engineering Journal, 2025)

Electrocatalytic synergistic degradation of tetracycline by low-energy-consumption Mn0.22-NiS nanosheet electrodes: Interface mechanism and toxicity analysis - Fan-Hao Hu; Qun-Feng Ye; Si-Ru Chen; Ya-Wen Yu; Hao Chen; Su-Fang Qin; Le-Xing You; Xiao-Chun Tian; Feng Zhao (Chemical Engineering Journal, 2025)

Carnosic Acid Attenuated the Motor Impairment by Bisphenol A is Related to the Regulation of Autophagy Through Parkin in In Vitro and In Vivo - Chun-Huei Liao; Ya-Chen Shih; Hsi-Yun Huang; Jing-Wei Chen; Shao-I Hsu; Chiao-Ni Lai; Ru-Huei Fu; Chia-Wen Tsai (Molecular Neurobiology, 2025)

Efficient Microbial Production of Selenium Nanoparticles by Selenium-Tolerant Alcaligenes sp. HZ-9-3-3 - Omer Hassan Ali Hassan; Ya-Ru Wei; Zai-Ping Feng; Jia-Mei Pei; Jia-Nan Xu; Wen-Tao Du; Qiang-qiang Gou; Wen-Di Wang; Xue Zhao; Qin-Cui Shi; Xin-Guo Zhang (Current Microbiology, 2025)

TISCalling: leveraging machine learning to identify translational initiation sites in plants and viruses - Ming-Ren Yen; Ya-Ru Li; Chia-Yi Cheng; Ting-Ying Wu; Ming-Jung Liu (Plant Molecular Biology, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Engineering an Ag2Se@PANi core–shell nanozymes – Klebsiella pasteurii hybrid system with enhanced ammonia synthesis - Meng-Xin Zhao; Si-Ru Chen; Bo Hu; Hao Chen; Ya-Xuan Xiao; Ting-Ting Liu; Shan-Shan Hu; Su-Fang Qin; Xuee Wu; Le-Xing You; Feng Zhao (Bioresource Technology, 2025)

Four saprobic species associated with Mahonia in Guizhou Province, China - Ya-Ru Sun; Kevin D. Hyde; Ning-Guo Liu; Fatimah O. Al-Otibi; Yong Wang; Ruvishika S. Jayawardena (Mycological Progress, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Functional analysis of Ophraella communa Lesage OcomOBP11 in recognition of Ambrosia artemisiifolia L. volatiles - Yang Yue; Chao Ma; Yan Zhang; Wei-hua Ma; Jing-jing Wang; Zhen-ya Tian; Guang-mei Chen; Ru-wen Li; Jin-hua Li; Jing-fang Yang; Zhong-shi Zhou (Pesticide Biochemistry and Physiology, 2025)

Poly (sodium acrylate-acrylamide) hydrogels for enrichment and purification of microalgal biomass in an open system: performance optimization and mechanistic analysis - Cong-Cong Tang; Yong-Qi Cheng; Sheng-Long Chen; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Journal of Environmental Management, 2025)

Effects of proteolysis pretreatment on the formation, structural changes and emulsifying properties of rice glutelin amyloid-like fibrils - Yi-Xuan Jiang; Ya-Ru Wang; Qin Yang; Xiao-Hong Yu; Han-Qing Chen (Food Chemistry, 2025)

A review on the genus Melodinus: traditional uses, phytochemical diversity and pharmacological activities of indole alkaloids - Si-Fan Teng; Fang-Ru Li; Qi-Min Cui; Afsar Khan; Ting He; Xiao-Dong Luo; Ya-Ping Liu; Gui-Guang Cheng (Phytochemistry Reviews, 2025)

Protective role of Tongxinluo in mitigating myocardial fibrosis in mice with acute myocardial infarction via neuregulin-1 upregulation and Inhibition of endothelium-interstitial transition - Zhen Li; Yu-jie Yin; Ya-ru Wei; Yi Liu; Ning-xin Han; Xiao-qi Wang; Yuan-jie Hao; Ya-fen Wang; Yun-long Hou; Zhen-hua Jia (Journal of Molecular Histology, 2025)

Exploring the multifaceted roles of histone deacetylase inhibitor vorinostat in the cell growth, mycelial morphology, pigments, and citrinin biosynthesis of Monascus purpureus - Run-Ya Li; Chen-Yu Zhang; Shaoxiang Xiao; Xin-Yi Liu; Ru-Xue Li; Jing Li; Hao Li; Jun Liu (Archives of Microbiology, 2025)

Characterization of the gut microbiota in drug abuse: prediction, prevention, and personalized medicine to benefit affected populations - Xin Wang; Ya-Jie Yu; Cai Liao; Xiao-Ru Liu; Rui Yu; Yun Wang (EPMA Journal, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Rapid and visual detection of the strawberries pathogenic fungi Fusarium oxysporum and Colletotrichum siamense by one-pot LAMP-CRISPR/Cas12b - Ya-Ru Tian; Dong-Lan Tang; Tian-Qi Wang; Jia-Yue Chen; Yan-Fang Dong; Xin-Yu Ying; Dan Zhang; Wen-Jing Wang; Zhi-Dan Luo (Journal of Plant Diseases and Protection, 2025)

Emergency control of dinoflagellate bloom in freshwater with chlorine enhanced by solar radiation: Efficiency and mechanism - Ru Wang; Ya Cheng; Qiqi Wan; Ruihua Cao; Jie Cai; Tinglin Huang; Gang Wen (Water Research, 2024)

Cadmium causes cerebral mitochondrial dysfunction through regulating mitochondrial HSF1 - Chen-Xi Li; Milton Talukder; Ya-Ru Xu; Shi-Yong Zhu; Yu-Xiang Wang; Jin-Long Li (Environmental Pollution, 2024)

Trichoderma harzianum promoting chrysanthemum cutting rooting and reshaping microbial communities in endophytic and rhizosphere environments - Ya-Jie Wu; Murad Muhammad; Yu Jiao; Xiu Chen; Hai-Long Wang; Chun-Mei Lu; Xiao-Ming Wang; Guo-Xing Zhu; Kai-Qing Liu; Yue Zhang; Zi-Chao Liu; Zhi-Xing Chen; et al. (Applied Soil Ecology, 2024)

Promoting symbiotic relationship between microalgae and bacteria in wastewater treatment processes: Technic comparison, microbial analysis, and future perspectives - Cong-Cong Tang; Ya-Ru Hu; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Chemical Engineering Journal, 2024)

Bi2O3/Bi@CSs achieved by shock-type heating for fast and long-lasting sodium ion battery - Ya Ru Pei; Xue Jing Yang; Wu Bin Wan; Hai Ming Huang; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2024)

One new 12, 8-guaianolide sesquiterpene lactone with antihyperglycemic activity from the roots of Cichorium intybus - Xiu-hua Meng; Yin-an Pan; Han Lv; Xiao-qin Ding; De-quan Yin; Ya-nan Gai; Guan-ting Niu; Bing-ru Ren; Xiao-guo Qian; Jian Chen (Natural Product Research, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Molecular insights into the interactions of theaflavin and epicatechin with different lipid bilayer membranes by molecular dynamics simulation - Rong-zu Nie; Huo-min Luo; Jing-yu Chen; Li-heng Sun; Zi-bo Wang; Zhen-ping Zhang; Ya-ru Bao (Chemistry and Physics of Lipids, 2024)

Development of the near-infrared fluorescence probe for detection of ONOO− and its application in vitro and vivo - Ya-Jing Shang; Yuan-Yuan Li; Jia-Ling Hu; Yi-Ru Wang; Sheng-Tao Li; Xing-Hu Wu; Ai-Hong Zhang; Yu-Wei Tan; Ting Liang; Xiao-Bo Zhu; Yan-Fei Kang (Analytica Chimica Acta, 2024)

Nano‑selenium alleviates cadmium-induced blood-brain barrier destruction by restoring the Wnt7A/β-catenin pathway - Chen-Xi Li; Milton Talukder; Zhao-Yi Wang; Shi-Yong Zhu; Ya-Ru Xu; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Comprehensive analysis of metal(loid)s and associated metal(loid) resistance genes in atmospheric particulate matter - Xiu-Peng Liang; He-Jing Wang; Jie-Ru Zheng; Xiao-Ru Wang; Dao-Ming Lin; Ya-Qing Wu; Rui-Lian Yu; Gong-Ren Hu; Yu Yan (Science of The Total Environment, 2024)

Hydroxyl-containing triazine-based conjugated microporous polymers for solid phase extraction of fluoroquinolone antibiotics in the environment and food samples - Lu-Shu Meng; Xiao-Li Wang; Xia Wang; Lei Ji; Lei-Lei Wang; Ya-Qi Cai; Ru-Song Zhao (Food Chemistry, 2024)

Identification and functional analyses of CD4-1+ cells in grass carp (Ctenopharyngodon idella) - Xue-Qing Han; Yi-Ru Pan; Ya-Qin Zhong; Tian-Tian Tian; Xun Liu; Xu-Jie Zhang; Yong-An Zhang (Fish & Shellfish Immunology, 2024)

Adsorption Kinetics and Stabilization Effects of Various Forms of Phosphorus on Schwertmannite - Shuqin Bai; Ru Ya; Shuxuan Chen; Niqi Ao; Yiwen Wu; Qiyao Sun; Han Yang; Shuangfeng Zhao (Water, Air, & Soil Pollution, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Poleward migration of tropical corals inhibited by future trends of seawater temperature and calcium carbonate (CaCO3) saturation - Ya-Yi Huang; Ting-Ru Chen; Kim Phuong Lai; Chao-Yang Kuo; Ming-Jay Ho; Hernyi Justin Hsieh; Yi-Chia Hsin; Chaolun A. Chen (Science of The Total Environment, 2024)

Unraveling the effect of combined heat and high-pressure homogenization treatment on the improvement of chickpea protein solubility from the perspectives of colloidal state change and structural characteristic modification - Yu Wang; Jing-jing Yuan; Ya-ru Zhang; Xing Chen; Jia-le Wang; Bo Chen; Ke Li; Yan-hong Bai (Food Chemistry, 2024)

Ovalbumin amyloid-like fibrils/resveratrol self-assembling hydrogel: Preparation, characterization and formation mechanism - Ya-Ru Wang; Qin Yang; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Effect of bovine hide gelatin antifreeze peptides on the quality of frozen dough treated with freeze-thaw cycles and its steamed bread - Chun-Chun Zhang; Ya-Ru Wang; Qin Yang; Han-Qing Chen (Journal of Cereal Science, 2024)

Pretreatment with low-frequency magnetic fields can improve the functional properties of pea globulin amyloid-like fibrils - Qing-Qing Liu; Qin Yang; Ya-Ru Wang; Yi-Xuan Jiang; Han-Qing Chen (Food Chemistry, 2024)

Ultrasound-regulated fibrillation of arachin: Structural characteristics, foaming and emulsifying properties - Qin Yang; Ya-Ru Wang; Qing-Qing Liu; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Role of phosphate in microalgal-bacterial symbiosis system treating wastewater containing heavy metals - Cong-Cong Tang; Ya-Ru Hu; Min Zhang; Sheng-Long Chen; Zhang-Wei He; Zhi-Hua Li; Yu Tian; Xiaochang C. Wang (Environmental Pollution, 2024)

CircRNA: a rising therapeutic strategy for lung injury induced by pulmonary toxicants - Cai Liao; Zhen-Wei He; Rui Yu; Ya-Jie Yu; Xiao-Ru Liu; De-Lei Kong; Yun Wang (Archives of Toxicology, 2024)

Di (2-ethylhexyl) phthalate induced lipophagy-related renal ferroptosis in quail (Coturnix japonica) - Yu Zhu; Xiang-Yu Ma; Ling-Ge Cui; Ya-Ru Xu; Chen-Xi Li; Milton Talukder; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Insights into the response of nitrogen metabolism to sulfamethoxazole contamination in constructed wetlands with varied substrates - Ya-Ru Zhang; Jia-Min Xu; Hao-Ran Xu; Guo-Dong Zhang; Xian-Bin Liu; Hao-Yi Cheng (Bioresource Technology, 2024)

Risk Assessment for Recreational Activities in the Coastal Ocean - Hui-Chieh Chuang; Dong-Jiing Doong; Chung-Ru Ho; Ya-Hui Ho (Journal of Marine Science and Engineering, 2024)
Ocean recreational activities (ORAs), including swimming, surfing, diving, paddleboarding, etc., in global marine areas are becoming increasingly popular. However, there are potential risks in coastal ocean environments. This study aims to establish a framework for assessing the risk according to the joint hazard and vulnerability levels of the ORA environment. Important factors include meteo-ocean conditions, geographic features, biological and chemical characteristics, and records of historical accidents, as well as social, environmental and tourist perceptions. The fuzzy Delphi method (FDM) is used to screen the representative factors, followed by using the analytical hierarchy process (AHP) to determine the weight of each factor. The results show that 9 hazard factors and 12 vulnerability factors are dominant. The framework is applied to 307 beaches in Taiwan, and 8% of them are categorized as very high risk and 13% as very low risk for ORAs. A risk map that displays the hazard, vulnerability, and overall risk levels is presented to tourists to provide quick access to risk information.

Scaling and cleaning of silica scales on reverse osmosis membrane: Effective removal and degradation mechanisms utilizing gallic acid - Shuqin Bai; Jue Han; Niqi Ao; Ru Ya; Wei Ding (Chemosphere, 2024)

Quantitative analysis of infectious precocity virus load and stunted growth syndrome via an immunohistochemical assay and reverse transcriptase quantitative real-time PCR in Macrobrachium rosenbergii - Yun-Ru Chiang; Ya-Yun Lu; Han-You Lin (Aquaculture, 2024)

Enhanced solubility, thermal stability and antioxidant activity of resveratrol by complexation with ovalbumin amyloid-like fibrils: Effect of pH - Ya-Ru Wang; Qin Yang; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Iodine Acetonitrile as a Drinking Water Disinfectant Showed a Potential Toxic Effect on Organism - Ya-Ping Li; Jie-Wen Cai; Pin-Ying Su; Shi-Ming Xie; Jia-Xuan Lai; Zi-Ru Xian; Jing-Da Qiao (Water, Air, & Soil Pollution, 2024)

Inflammation and Brain Structure in Alzheimer’s Disease and Other Neurodegenerative Disorders: a Mendelian Randomization Study - Wei-Shi Liu; Ya-Ru Zhang; Yi-Jun Ge; Hui-Fu Wang; Wei Cheng; Jin-Tai Yu (Molecular Neurobiology, 2024)

Factors affecting the occurrence and accumulation of perfluoroalkyl acids in indoor dust in Tainan, Taiwan - Yi-Wei Biao; Jing-Ya Xu; Wan-Ru Chen (Chemosphere, 2024)

Long-term exposure to the mixture of phthalates induced male reproductive toxicity in rats and the alleviative effects of quercetin - Li-Lan Liu; Jun-Zhe Yue; Zhen-Yu Lu; Ru-Ya Deng; Can-Can Li; Ye-Na Yu; Wen-Jin Zhou; Min Lin; Hai-Tao Gao; Jiaming Liu; Ling-Zi Xia (Toxicology and Applied Pharmacology, 2024)

Formation and structural characteristics of pea globulin amyloid-like fibrils pretreated with low-frequency magnetic field - Qing-Qing Liu; Qin Yang; Ya-Ru Wang; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Impact of uncertainty induced by fatality function on future tropical cyclone risk assessment - Rumei Tang; Jidong Wu; Wei Ding; Ya Ru (Science of The Total Environment, 2023)

An Aggregation-induced Emission Probe to Detect the Viscosity Change in Lipid Droplets during Ferroptosis - Bing Zhang; Ya-Ru Zhang; Chang-Jiang Wang; Jing-Yi Jin (Journal of Fluorescence, 2023)

Excellent hydration properties and oil holding capacity of citrus fiber: Effects of component variation and microstructure - Chun-ai He; Jun-ru Qi; Jin-song Liao; Ya-ting Song; Chun-lin Wu (Food Hydrocolloids, 2023)

Prenatal and postnatal exposure to heavy metals in PM2.5 and autism spectrum disorder - Hao-Hsuan Lin; Chau-Ren Jung; Chuan-Yao Lin; Ya-Chu Chang; Chia-Yun Hsieh; Pei-Chuan Hsu; Bao-Ru Chuang; Bing-Fang Hwang (Environmental Research, 2023)

Ozone exposure associates with sperm quality indicators: Sperm telomere length as a potential mediating factor - Zhong-Hua Lu; Bin Sun; Yi-Xin Wang; Ya-Ru Wu; Yu-Jie Chen; Sheng-Zhi Sun; Shi-Jia Liang; Song Xu; Hao Chang; Heng-Gui Chen; Jie Zhang (Journal of Hazardous Materials, 2023)

Self-assembly and interaction mechanisms of edible dock protein and flavonoids regulated by the phenolic hydroxyl position - Qian Zhou; Xiao-Jie Wang; Jing Li; Yu-Ru Wu; Wei Wang; Zhen-Yu Yu; Ya-Qing Xiao; Ying-Nan Liu; Shi-Yi Li; Ming-Ming Zheng; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2023)

Fungal strain improvement for efficient cellulase production and lignocellulosic biorefinery: Current status and future prospects - Jie Yang; Hou-Ru Yue; Li-Ya Pan; Jia-Xun Feng; Shuai Zhao; Surisa Suwannarangsee; Verawat Champreda; Chen-Guang Liu; Xin-Qing Zhao (Bioresource Technology, 2023)

Effects of contrasting tillage managements on the vertical distribution of plant- and microbial-derived carbon in rice paddy - Jian-Ying Qi; Xiang-Bin Yao; Mei-Yang Duan; Xiang-Wen Huang; Mei-Yi Fan; Ya Yang; Hao-Wen Luo; Xiang-Ru Tang (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Effects of exposure to chlorinated paraffins on human health: A scoping review - Jing-Wen Huang; Ya-Ying Bai; Mohammed Zeeshan; Ru-Qing Liu; Guang-Hui Dong (Science of The Total Environment, 2023)

Pollinium development and sporoderm structure of Dendrobium officinale - Yi Feng Cui; Ting Zhou; Ya Ru Wei; De Quan Wang; Wen Yu Liang; Shu Juan Yang (Flora, 2023)

Thymic tuft cells: potential “regulators” of non-mucosal tissue development and immune response - Jun Sun; Ming-xin Li; Yi-meng Xie; Ya-ru Zhang; Yu-rong Chai (Immunologic Research, 2023)

CAT Interruption as a Protective Factor in Chinese Patients with Spinocerebellar Ataxia Type 1 - Ya-Ru Shao; Jin-Yang Yu; Yin Ma; Yi Dong; Zhi-Ying Wu (The Cerebellum, 2023)

Effects of fungal agents and biochar on odor emissions and microbial community dynamics during in-situ treatment of food waste - Shu-Ping Zou; Ru-Sheng Liu; Yu Luo; Chun-Tao Bo; Su-Qin Tang; Ya-Ping Xue; Yu-Guo Zheng (Bioresource Technology, 2023)

A single fluorescent probe reveals changes in endoplasmic reticulum–mitochondria contact in hepatocytes during ferroptosis - Ling-Li Wang; Ya-Ru Zhang; Ming-Hua Zheng; Xuan Wang; Xue Wu; Jing-Yi Jin (Chemical Engineering Journal, 2023)

4-OI ameliorates bleomycin-induced pulmonary fibrosis by activating Nrf2 and suppressing macrophage-mediated epithelial-mesenchymal transition - Ya-xian Wu; Ya-ru Zhang; Feng-juan Jiang; Shuai He; Yan-li Zhang; Dan Chen; Ying Tong; Yun-juan Nie; Qing-feng Pang (Inflammation Research, 2023)

Comparison of the assembly behavior and structural characteristics of arachin and conarachin amyloid-like fibrils - Qin Yang; Ya-Ru Wang; Ya-Nan Du; Han-Qing Chen (Food Hydrocolloids, 2023)

Cadmium aggravates the blood-brain barrier disruption via inhibition of the Wnt7A/β-catenin signaling axis - Chen-Xi Li; Milton Talukder; Ya-Ru Xu; Shi-Yong Zhu; Ying-Xin Zhao; Jin-Long Li (Environmental Pollution, 2023)

Circulating polyunsaturated fatty acids, fish oil supplementation, and risk of incident dementia: a prospective cohort study of 440,750 participants - Yu He; Shu-Yi Huang; Hui-Fu Wang; Wei Zhang; Yue-Ting Deng; Ya-Ru Zhang; Qiang Dong; Jian-Feng Feng; Wei Cheng; Jin-Tai Yu (GeroScience, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Characteristics of dynamic shear modulus and damping ratio and the structural formula of EPS particles lightweight soil - Tian-shun Hou; Yi-xiang Cui; Xing-ru Pan; Ya-sheng Luo; Qian Liu (Soil Dynamics and Earthquake Engineering, 2023)

Chitosan can improve the storage stability of ovalbumin fibrils at pH higher than isoelectric point - Ya-Ru Wang; Qin Yang; Ya-Nan Du; Han-Qing Chen (Food Hydrocolloids, 2023)

Heat-induced arachin and basil seed gum composite gels improved by NaCl and microbial transglutaminase: Gelling properties and structure - Qin Yang; Ya-Ru Wang; Ya-Nan Du; Han-Qing Chen (Food Hydrocolloids, 2023)

Insights into the influence on 2,4,6-trichlorophenol microbial reductive dechlorination process by exposure to microplastics - Jia-Qi Yang; Zhi-Ling Li; Bin Wu; Ya-Ru Jin; Di Cao; Jun Nan; Xue-Qi Chen; Wen-Zong Liu; Shu-Hong Gao; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

Additional ratios of hydrolysates from lignocellulosic digestate at different hydrothermal temperatures influencing anaerobic digestion performance - Jing Wang; Nannan Zhao; Xuan Zhang; Lei Jiang; Ya-Ru Kang; Yi-Xuan Chu; Ruo He (Environmental Science and Pollution Research, 2022)

Siccirubricoccus soli sp. nov., a novel bacterial species isolated from Jiaozi Mountain soil - Guo-Xing Zhu; Ya-Jie Wu; Yan-Ru Cao; Bing-Jun Fan; Yu Jiao; Xiu-Li Hou; Zi-Chao Liu; Yue Zhang; Jiang-Bo He; Lian-Ming Liang (Antonie van Leeuwenhoek, 2022)

Strength and deformation behavior of columnar jointed rock masses under different confining pressures - Zhi-nan Lin; Hai-feng Long; Wei-ya Xu; Ru-bin Wang; Shi-hong Feng (Arabian Journal of Geosciences, 2022)

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Novel Alcaligenes ammonioxydans sp. nov. from wastewater treatment sludge oxidizes ammonia to N 2 with a previously unknown pathway - Meng‐Ru Wu; Ting‐Ting Hou; Ying Liu; Li‐Li Miao; Guo‐Min Ai; Lan Ma; Hai‐Zhen Zhu; Ya‐Xin Zhu; Xi‐Yan Gao; Craig W. Herbold; Michael Wagner; De‐Feng Li; et al. (Environmental Microbiology, 2021)
Summary Heterotrophic nitrifiers are able to oxidize and remove ammonia from nitrogen‐rich wastewaters but the genetic elements of heterotrophic ammonia oxidation are poorly understood. Here, we isolated and identified a novel heterotrophic nitrifier, Alcaligenes ammonioxydans sp. nov. strain HO‐1, oxidizing ammonia to hydroxylamine and ending in the production of N 2 gas. Genome analysis revealed that strain HO‐1 encoded a complete denitrification pathway but lacks any genes coding for homologous to known ammonia monooxygenases or hydroxylamine oxidoreductases. Our results demonstrated strain HO‐1 denitrified nitrite (not nitrate) to N 2 and N 2 O at anaerobic and aerobic conditions respectively. Further experiments demonstrated that inhibition of aerobic denitrification did not stop ammonia oxidation and N 2 production. A gene cluster ( dnfT1RT2ABCD ) was cloned from strain HO‐1 and enabled E . coli accumulated hydroxylamine. Sub‐cloning showed that genetic cluster dnfAB or dnfABC already enabled E . coli cells to produce hydroxylamine and further to 15 N 2 from ( 15 NH 4 ) 2 SO 4 . Transcriptome analysis revealed these three genes dnfA , dnfB and dnfC were significantly upregulated in response to ammonia stimulation. Taken together, we concluded that strain HO‐1 has a novel dnf genetic cluster for ammonia oxidation and this dnf genetic cluster encoded a previously unknown pathway of di rect amm onia ox idation (Dirammox) to N 2 .

Effects of different pretreatment methods on biogas production and microbial community in anaerobic digestion of wheat straw - Ya-Ru Kang; Yao Su; Jing Wang; Yi-Xuan Chu; Guangming Tian; Ruo He (Environmental Science and Pollution Research, 2021)

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

A rapid and accurate method for identifying sexuality of Indarbela obliquifasciata Mell (Lepidoptera, Metarbelidae) adults and pupae - Li-Zhi Huo; Long-Hua Sun; Jing-Ai Zhang; Chao Wu; Ya-Hui Hou; Yong-Yue Wang; Zhi-Jie Li; Jia-Ru Deng; Si-Meng Yang; Ke-Ke Bi (International Journal of Tropical Insect Science, 2021)

First report of Athelia rolfsii causing collar rot of Phalaenopsis orchid in Taiwan - Shih-Ya Chiu; Yi-Ru Lai; Wen-Shi Tsai; Chien-Jui Huang (Journal of Plant Pathology, 2021)

Decreased KLHL3 expression is involved in the activation of WNK-OSR1/SPAK-NCC cascade in type 1 diabetic mice - Qin Guo; Ya Zhang; Geng-Ru Jiang; Chong Zhang (Pflügers Archiv - European Journal of Physiology, 2021)

Factors Associated with Intergenerational Instability of ATXN3 CAG Repeat and Genetic Anticipation in Chinese Patients with Spinocerebellar Ataxia Type 3 - Yi-Chu Du; Yin Ma; Ya-Ru Shao; Shi-Rui Gan; Yi Dong; Zhi-Ying Wu (The Cerebellum, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

Endophytic colonization by Beauveria bassiana increases the resistance of tomatoes against Bemisia tabaci - Qiu-Yang Wei; Ya-Ying Li; Chen Xu; Yi-Xia Wu; Ya-Ru Zhang; Huai Liu (Arthropod-Plant Interactions, 2020)
Beauveria bassiana , an entomopathogenic fungus, can exist asymptomatically as an endophyte in many plants. This study aimed to determine the efficiency of B. bassiana colonization of tomato plants using different inoculation methods, and how colonization of the host plant affects the key pest of tomato, the whitefly Bemisia tabaci . To confirm fungal colonization efficiency, nested PCR technique was used to detect B. bassiana sequences in Solanum lycopersicum . Distribution of the fungus within the plant parts was determined by selective medium. Tomato growth parameters were determined with plants that had been inoculated using direct spraying or irrigation of the rhizosphere. B. tabaci performance assays were carried out in a cage, and preference to treatments was determined using Y-tube olfactometer studies. Results show that B. bassiana can effectively colonize tomato, with colonization rate using leaf spraying reaching 100% within 14 days. Fungal presence was not uniformly distributed among plant parts, but was biased towards the inoculation sites. For inoculation, conidial suspension sprayed at 1 × 10 8 conidia/ml resulted in the highest number of isolated colonies in leaf tissue, 8.5 ± 2.02 colonies per 2 g of fresh tissue ( F 4,19 = 2.779, P = 0.045), and reached the lowest with root treatment. Although only small differences were observed among the growth indicators, leaf spray inoculation resulted in a significant positive influence on plant growth (PC1 55.7% contributions scores = 2.645) in further Principal component analysis. As for the feeding selectivity, B. tabaci preferred uninoculated plants. In Y-tube olfactometer assay, 80.5% of adults selected uninoculated plants. These findings add to the understanding of the interactions between B. bassiana and plants and indicate the potential of expanding the use of entomopathogenic fungi for crop protection.

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Effects of oxygen tension on the microbial community and functional gene expression of aerobic methane oxidation coupled to denitrification systems - Yi-Xuan Chu; Ruo-Chan Ma; Jing Wang; Jia-Tian Zhu; Ya-Ru Kang; Ruo He (Environmental Science and Pollution Research, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Use of discrete choice experiments to facilitate design of effective environmentally friendly agricultural policies - Na-na Wang; Liang-guo Luo; Ya-ru Pan; Xue-mei Ni (Environment, Development and Sustainability, 2019)

Quantification of cardiac pumping mechanics in rats by using the elastance–resistance model based solely on the measured left ventricular pressure and cardiac output - Chih-Hsien Wang; Ru-Wen Chang; En-Ting Wu; Chun-Yi Chang; Hsien-Li Kao; Ming-Shiou Wu; Ya-Jung Cheng; Yih-Sharng Chen; Kuo-Chu Chang (Pflügers Archiv - European Journal of Physiology, 2019)

Geomorphic features of Quaternary glaciation in the Taniantaweng Mountain, on the southeastern Qinghai-Tibet Plateau - Wei Zhang; Le Chai; Ian S Evans; Liang Liu; Ya-peng Li; Jing-ru Qiao; Qian-yu Tang; Bo Sun (Journal of Mountain Science, 2019)

Comparative proteomic analysis of Nostoc flagelliforme reveals the difference in adaptive mechanism in response to different ultraviolet-B radiation treatments - Shi-gang Shen; Rong-jun Guo; Rong-rong Yan; Yi-kai Wu; Dong-xue Zhao; Ya-hui Lin; He-xin Lv; Shi-ru Jia; Pei-pei Han (Molecular Biology Reports, 2018)

The effect and biological mechanism of granular sludge size on performance of autotrophic nitrogen removal system - Xing Ya-juan; Ji Jun-yuan; Zheng Ping; Wang Lan; Ghulam Abbas; Jiqiang Zhang; Wang Ru; He Zhan-fei (Biodegradation, 2018)

Characteristics and mechanisms of the diurnal variation of winter precipitation in Taiwan - Wan‐Ru Huang; Ya‐Hui Chang (International Journal of Climatology, 2018)
Using gridded precipitation data remapping from rain‐gauge observations of the time period of 2001–2015 winter months (December, January and February), this study examines the spatio‐temporal characteristics of the climatological diurnal winter precipitation in Taiwan. Our results show that the timings of the maximum values of the diurnal precipitation in Taiwan exhibit clear east–west regional differences, with night‐time maxima over eastern Taiwan but early morning maxima over western Taiwan. Analyses also show that the climatological characteristics of diurnal winter precipitation documented in this study are not controlled by some unusual, heavy precipitation events and can be seen as the common features. By examining the changes in meteorological variables (including winds, relative humidity and temperature) extracted from the in situ observations and the MERRA (Modern‐Era Retrospective Analysis for Research and Applications) reanalysis, this study further suggests that (a) the radiative cooling effect and (b) the surface wind convergence induced by the interaction between the local orography, the local land–sea breeze and the large‐scale diurnal circulation changes over the East Asian–western North Pacific (EAWNP) region are two of the possible formation mechanisms responsible for the spatio‐temporal differences of the climatological diurnal winter precipitation in Taiwan. This finding sheds light on the importance of understanding the role of the large‐scale diurnal circulation changes over the EAWNP region in modulating local diurnal precipitation properties during the winter months.

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

Impact of boreal summer intra‐seasonal oscillations on warm season diurnal convection activity in Taiwan - Wan‐Ru Huang; Ya‐Hui Chang (International Journal of Climatology, 2018)
Diurnal convection (DC), which is characterized by rainy days with maximum rainfall during the afternoon without strong synoptic disturbances, is the most frequently observed weather system that affects local rainfall in Taiwan. In this study, we investigate the impact of boreal summer intra‐seasonal oscillations (BSISOs) on the modulation of warm season (May–September) DC activities in Taiwan. Our analyses focus on (1) identifying the relationships between changes in DC characteristics (e.g. DC days and the mean rainfall intensities on DC days) and the phase evolutions of two types of BSISOs (including the 30–60‐day ISO named BSISO1 and the 10–30‐day ISO named BSISO2) and (2) the related maintenance mechanisms. Analyses of DC days demonstrate that the contribution of DC days to the total quantity of rainy days in Taiwan generally reaches a maximum value when Taiwan is being modulated by intensified southwesterly winds, intensified local sea breeze circulations, and intensified local thermal instabilities (i.e. phase 3 of BSISO1 and phase 7 of BSISO2). Analyses of the mean rainfall intensities on DC days show that maximum values are generally reached when the moisture convergence line propagates northwards over Taiwan (i.e. phase 1 of BSISO1 and phase 3 of BSISO2). Further examinations indicate that the abovementioned findings are not dependent upon the strengths of the BSISOs.

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Regulation of fine particulate matter (PM2.5) in the Pacific Rim: perspectives from the APRU Global Health Program - Chang-Fu Wu; Alistair Woodward; Ya-Ru Li; Haidong Kan; Rajasekhar Balasubramanian; Mohd Talib Latif; Mazrura Sahani; Tsun-Jen Cheng; Chia-Pin Chio; Nutta Taneepanichskul; Ho Kim; Chang-Chuan Chan; et al. (Air Quality, Atmosphere & Health, 2017)

Zircon U–Pb dating of eclogite from the Qiangtang terrane, north-central Tibet: a case of metamorphic zircon with magmatic geochemical features - Qing-guo Zhai; Bor-ming Jahn; Xian-hua Li; Ru-yuan Zhang; Qiu-li Li; Ya-nan Yang; Jun Wang; Tong Liu; Pei-yuan Hu; Suo-han Tang (International Journal of Earth Sciences, 2017)

Assessment of Photodegradation of Herbicide Prometryn in Soil - Chen Jiang; Xue Jing Li; Ya Ru Wang; Li Ya Ma; Ya Kun Wang; Yi Chen Lu; Hong Yang (Water, Air, & Soil Pollution, 2017)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Cytomolecular characterization and origin of de novo formed maize B chromosome variants - Ya-Ming Cheng; Ying-Ru Feng; Yao-Pin Lin; Shu-Fen Peng (Chromosome Research, 2016)

Pertrogenesis and tectonic implications of the late Jurassic basic rocks from the northern Shi‐Hang zone, Southeast China - Qing Zhou; Yao–hui Jiang; Shi–yong Liao; Peng Zhao; Ru–ya Jia; Zheng Liu; Guo–chang Wang; Chun–yu Ni (Island Arc, 2016)
The tectonic setting of the late mesozoic of South China is in a debate between two schools of thought: an intra‐continental rift zone along a passive continental margin or active rifting associated with subduction of the paleo‐Pacific Plate. In this study, we present new sensitive high‐resolution ion microprobe (SHRIMP) U‐Pb zircon ages, along with geochemical data of three basic dikes that cross‐cut the Dexing porphyry copper deposit. The deposit is the largest of its kind in eastern China and part of large scale mineralization associated with Mesozoic magmatic activity in the area. Our results indicate that the dikes were emplaced in the Late Jurassic with an average U‐Pb age of 153.5 ± 2.4 Ma. The intrusions have bulk ε Nd (t) of ca +0.7 and zircon ε Hf (t) value of +1.54 to +6.92. Based on relatively enriched light rare earth elements (LREE) and depleted high‐field‐strength elements (HFSE) abundances with pronounced negative Ta–Nb, Hf–Zr and Ti anomalies in multi‐element diagrams, we propose that these dikes were derived from a subduction‐modified lithospheric mantle source. The variability in Hf isotopes identifies some degree of crustal contaminations. Our data support a scenario with a back‐arc extensional setting or an intra‐arc rift environment associated with the westward subduction of the paleo‐Pacific Plate at or prior to the late Jurassic as the most likely cause for these subduction signatures.

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Investigation on time-dependent behaviour and long-term stability of underground water-sealed cavern - Huan-ling Wang; Wei-ya Xu; Long Yan; Qing-xiang Meng; Ru-bin Wang; Hai-bin Zhao; Wei-chau Xie (European Journal of Environmental and Civil Engineering, 2015)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

Isolation and characterisation of Bacillus spp. antagonistic to Vibrio parahaemolyticus for use as probiotics in aquaculture - Xue-Fei Liu; Ya Li; Jian-Rong Li; Lu-Yun Cai; Xiu-Xia Li; Jin-Ru Chen; Shu-Xia Lyu (World Journal of Microbiology and Biotechnology, 2015)

The relationship between the plant-encoded RNA-dependent RNA polymerase 1 and alternative oxidase in tomato basal defense against Tobacco mosaic virus - Yang-Wen-Ke Liao; Ya-Ru Liu; Jia-Yang Liang; Wen-Ping Wang; Jie Zhou; Xiao-Jian Xia; Yan-Hong Zhou; Jing-Quan Yu; Kai Shi (Planta, 2015)

CIC-3 chloride channel blockade protects mouse photoreceptor-derived 661W cells against ischemia-reperfusion-induced injury in vitro - Shi Wei Huang; Yuan Yin; Ya Juan Zheng; Ya Ru Dong (Molecular & Cellular Toxicology, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Umbelopsis changbaiensis sp. nov. from China and the typification of Mortierella vinacea - Ya-Ning Wang; Xiao-Yong Liu; Ru-Yong Zheng (Mycological Progress, 2014)

Origin of Middle Cambrian and Late Silurian potassic granitoids from the western Kunlun orogen, northwest China: a magmatic response to the Proto-Tethys evolution - Zheng Liu; Yao-Hui Jiang; Ru-Ya Jia; Peng Zhao; Qing Zhou; Guo-Chang Wang; Chun-Yu Ni (Mineralogy and Petrology, 2014)

Origin of Early Cretaceous high-K calc-alkaline granitoids, western Tibet: implications for the evolution of the Tethys in NW China - Yao-Hui Jiang; Zheng Liu; Ru-Ya Jia; Shi-Yong Liao; Peng Zhao; Qing Zhou (International Geology Review, 2014)

Petrogenesis and tectonic implications of early Silurian high-K calc-alkaline granites and their potassic microgranular enclaves, western Kunlun orogen, NW Tibetan Plateau - Ru-Ya Jia; Yao-Hui Jiang; Zheng Liu; Peng Zhao; Qing Zhou (International Geology Review, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Physiological roles of mycothiol in detoxification and tolerance to multiple poisonous chemicals in Corynebacterium glutamicum - Ying-Bao Liu; Ming-Xiu Long; Ya-Jie Yin; Mei-Ru Si; Lei Zhang; Zhi-Qiang Lu; Yao Wang; Xi-Hui Shen (Archives of Microbiology, 2013)

Mantle origin of the Dexing porphyry copper deposit, SE China - Qing Zhou; Yao-Hui Jiang; Hui-Hua Zhang; Shi-Yong Liao; Guo-Dong Jin; Peng Zhao; Ru-Ya Jia; Zheng Liu (International Geology Review, 2013)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Cloning and sequence analysis of chitin synthase gene fragments of Demodex mites - Ya-e Zhao; Zheng-hang Wang; Yang Xu; Ji-ru Xu; Wen-yan Liu; Meng Wei; Chu-ying Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Sociodemographic characteristics and risk factor analysis of Demodex infestation (Acari: Demodicidae) - Ya-e Zhao; Na Guo; Meng Xun; Ji-ru Xu; Mei Wang; Duo-lao Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Estimates of individuals exposed to human metapneumovirus in a community-based Taiwanese population in 1999 - Chung-Guei Huang; Kuo-Chien Tsao; Tzou-Yien Lin; Yhu-Chering Huang; Li-Ang Lee; Tzu-Hou Chen; Ya-Ling Huang; Shin-Ru Shih (Archives of Virology, 2010)

Therapeutic effect of microencapsulated porcine retinal pigmented epithelial cells transplantation on rat model of Parkinson’s disease - Hou-Liang Zhang; Jian-Jun Wu; Hui-Min Ren; Jian Wang; Ya-Ru Su; Yu-Ping Jiang (Neuroscience Bulletin, 2007)

Overexpression of lentivirus-mediated glial cell line-derived neurotrophic factor in bone marrow stromal cells and its neuroprotection for the PC12 cells damaged by lactacystin - Ya-Ru Su; Jian Wang; Jian-Jun Wu; Yan Chen; Yu-Ping Jiang (Neuroscience Bulletin, 2007)

Effect of banning vancomycin analogue avoparcin on vancomycin‐resistant enterococci in chicken farms in Taiwan - Tsai‐Ling Lauderdale; Yih‐Ru Shiau; Hui‐Ying Wang; Jui‐Fen Lai; I‐Wen Huang; Pei‐Chen Chen; Hong‐Yi Chen; Shiow‐Suey Lai; Ya‐Fang Liu; Monto Ho (Environmental Microbiology, 2007)
Summary Avoparcin, a vancomycin analogue, was banned as a feed additive in Taiwan in 2000. A nationwide surveillance was conducted to study the prevalence of vancomycin‐resistant enterococci (VRE) on chicken farms between 2000 and 2003. Among the 1021 E. faecalis and 967 E. faecium isolates studied, resistance to tetracycline, erythromycin, high‐level aminoglycosides, ciprofloxacin and chloramphenicol either increased or remained high except vancomycin. The proportion of VRE decreased, between 2000 and 2003, from 13.7% (22/161) to 3.7% (11/299) for E. faecalis , and 3.4% (4/119) to 0% (0/300) for E. faecium . Only 8.8% (7/80) of the chicken farms surveyed harboured VRE in 2003 compared with 25% (15/60) in 2000. All VRE were resistant to tetracycline and erythromycin. All VRE possess the vanA gene but nearly all (79 of 83 isolates) were susceptible to teicoplanin, indicating VanB phenotype. Some clones were detected from different farms in various regions over the years. We conclude that the frequency of VRE in chicken farms decreased in association with a ban on avoparcin; and the continued presence of VRE may be due to the ability of some strains to persist in the farms, transfer of vancomycin resistance determinants or co‐selection by the continued use of other antibiotics.